Efficiency and capacity of trawlers in West Coast Peninsular Malaysia - Muhammad Danial Abdullah,; Wan Rosmanira Ismail,; Aishah Najihah Alias, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study discusses the efficiency, capacity and capacity utilization of fish trawlers of various zones in the west coast of Peninsular Malaysia in 2011. Data for this study were obtained from the Department of Fisheries Malaysia. An input-oriented Data Envelopment Analysis (DEA) model assuming the constant return to scale (CRS) technology was used to measure the technical efficiency and an output-oriented DEA model based on variable returns to scale (VRS) was implemented for the efficiency of capacity and capacity utilization. The study found that nearly 80% of trawlers fishing on the West Coast of Peninsular Malaysia is efficient and have an average 0.90 capacity utilization. Only fish trawlers in Perlis C2 Zone, B Zone and C Zone in Kedah were inefficient and has excess capacity to be reduced respectively by 58%, 29% and 38%. Overall current capacity can be increased by 6.14% if the excess capacity have been overcome.